Proyek vlog untuk meningkatkan kreativitas siswa dalam pembelajaran sejarah (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
Project-Based Learning Model is considered an appropriate learning model in developing student’s creativity because the model will utilize ideas and the ideas of creative students in making an interesting project. In this study researcher using design research developed by Dave Ebbt by stages starting from the planning, implementation, observation, and reflection. Data collection techniques used are interviews, observation, and study the documentation. Furthermore, data collection tools used are observation, interview guidelines are guidelines, and also note field. Data collection techniques used are interviews, observation, and study the documentation. the selection of the projects that will be used to enhance creativity is considering based on the elements of creativity itself, namely Elaboration, Orisinilitas, flexibility, and Smooth as expressed by Guilford. Then the researchers considered the means of vlog learning the appropriate elements of creativity and have a closeness in the world of the students in the 21st century. Based on the results of the study, with the use of model learning project based learning-based vlog can be a solution to improve the creativity of students in learning history.
Keywords: creativity; history lesson; vlog